Experimental study on the triaxial compressive properties of UHPC with coarse aggregate steel slag micro powder under different confining pressures - Xianyuan Tang; Chenzhuo Feng; Bowen Ren; Changhong Zhou; Cong Peng (Scientific Reports)
Abstract In order to study the compressive properties of ultra-high performance concrete (UHPC) mixed with coarse aggregate and steel slag powder under different confining pressures, provide technical parameters for the application of UHPC in constrained structures such as steel pipes or stirrups, 20 UHPC specimens were made with 5 different mix proportions. Triaxial compressive tests were carried out under four confining pressures (0 MPa, 5 MPa, 10 MPa and 15 MPa) by using Rock Top full stress multi-field coupling triaxial apparatus, and the stress-strain curves of UHPC specimens were obtained, and the failure of UHPC specimens was analysed. The results show that under uniaxial condition, the UHPC test block of steel slag powder is in the form of longitudinal splitting failure, when the confining pressure is 5 MPa and 10 MPa, the test block is in the form of oblique shear failure, and when the confining pressure is 15 MPa, the test block is in the form of horizontal shear failure of multiple cracks in the middle. The stress-strain curve of UHPC steel slag powder is basically straight in the front section. When there is no confining pressure, the curve has obvious peaks, and the curve drops rapidly after the peak point. When the confining pressure value σ2 ≥ 5 MPa, with the increase of confining pressure value, the rising section and peak point of the curve increase, and the downward trend after the peak point slows down. The peak stress and strain increase with the increase of confining pressure, but the growth rate slows down slightly and the deformation ability increases. With the increase of crushed stone content, the peak stress and strain of the specimen gradually decrease under the same confining pressure. Adding steel fibre can effectively strengthen the bond between cement matrix and make the specimen have good ductility.